General Motors Futurama
Caption, "A 10-Story Entrance Canopy soars skyward to welcome some 100,000 persons a day who visit the General Motors Futurama at the New York World's Fair. A portion of the GM ""ride into tomorrow"" - most popular attraction at the fair - passes through the 110-ft. high steel framework which supports the cantilevered canopy. Designed by GM's Styling Staff, the 230,000-square-foot pavilion also houses a display of GM research in science and engineering and GM products. Flanked by two reflecting pools, the building entrance canopy is illuminated at night in an ever-changing panorama of color."